The internalisation of external costs of CO2 and pollutant emissions from passenger cars - Kaplanović, Snežana; Mijailović, Radomir (Technological and Economic Development of Economy, 2012)
The paper's goal is to unify practical and theoretical aspects of internalisation of external costs, in line with the “polluter pays” and “user pays” principles. Due to the impossibility of applying an ideal economic solution for internalisation of external costs, alternative solutions have to be developed and implemented. One of the possible solutions for internalisation of external costs of CO2 and pollutant emissions from passenger cars is presented in this paper. It is a new methodology for calculating annual circulation taxes on passenger cars. This methodology, besides CO2, also takes into account the pollutants whose emissions are regulated by the Euro standards (CO, HC, NOx and PM), as well as the vehicle age and kilometres driven. The proposed methodology has been tested on some of the best-selling passenger cars in Europe. The results of analysis show significant differences between our methodology and the methodologies that are used in five European countries (Ireland, the United Kingdom, Malta, Luxembourg and Sweden), which use the CO2 emissions as a reference value for their calculation. Also, we have proved that the annual circulation tax, calculated using our methodology, provide better internalisation of external costs compared to the fuel tax.